ANALYSIS OF HATE SPEECH FRAMING IN RELATION TO THE 80TH INDEPENDENCE DAY LOGO ON INSTAGRAM SOCIAL MEDIA - Farendika, I Nyoman; Pratiwi, Nuning Indah (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This study aims to examine how hate speech is constructed and framed by netizens toward the 80th Indonesian Independence Day (HUT RI) logo on Instagram. Employing a descriptive qualitative approach and Robert Entman’s framing analysis model which encompasses four key elements: defining problems, diagnosing causes, making moral judgments, and offering treatment recommendations this research explores the construction of digital public discourse through content observation, in-depth interviews with key informants, and document analysis. The findings reveal that the framing of hate speech manifests in two primary forms, namely symbolic and linguistic, expressed through humor, sarcasm, and parody visuals that highlight public resistance toward the government. The public frames the logo as a symbol of governmental failure to represent the spirit of independence, thus positioning hate speech as a form of social and political expression of collective disappointment. This phenomenon indicates that the digital sphere has evolved into an arena where the meaning of freedom of expression shifts from rational criticism toward emotional and resistant expression. The study underscores the importance of digital literacy and ethical public communication to ensure that freedom of expression on social media remains productive, balanced, and reinforces national values in the digital era